2006
DOI: 10.1124/mol.106.029926
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Folding of P-Glycoprotein and Cystic Fibrosis Transmembrane Conductance Regulator Truncation Mutants with Pharmacological Chaperones

Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) and P-glycoprotein (P-gp) are ATP-binding cassette (ABC) transporters that have two transmembrane domains (TMDs) and two nucleotide-binding domains (NBDs). Defective folding of CFTR lacking phenylalanine 508 (⌬Phe508) in NBD1 is the most common cause of cystic fibrosis. The Phe508 position seems to be universally important in ABC transporters because deletion of the equivalent residue (Tyr490) in P-gp also inhibits maturation of the protein. The pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 39 publications
2
75
1
Order By: Relevance
“…In related studies, we showed in pulsechase experiments that Corr-4a increased accumulation of CFTRV232D due to an increase in folding efficiency and not increased expression (9). In addition, we found that VRT-532, a compound identified as a potentiator of CFTR P o , was associated with a modest increase in CFTRV232D band C expression, as was reported for CFTR⌬F508 (27). Importantly, the CFTRV232D trafficking defect was surmounted by Corr-4a treatment, with the folded protein achieving CFTR expression levels in HEK-293 cells.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…In related studies, we showed in pulsechase experiments that Corr-4a increased accumulation of CFTRV232D due to an increase in folding efficiency and not increased expression (9). In addition, we found that VRT-532, a compound identified as a potentiator of CFTR P o , was associated with a modest increase in CFTRV232D band C expression, as was reported for CFTR⌬F508 (27). Importantly, the CFTRV232D trafficking defect was surmounted by Corr-4a treatment, with the folded protein achieving CFTR expression levels in HEK-293 cells.…”
Section: Resultssupporting
confidence: 49%
“…Treatment with Corr-4a increased CFTRV232D protein expression and channel activity to levels that were similar to those of CFTR. Moreover, 4-methyl-2-(5-phenyl-1H-pyrazol-3-yl)-phenol (VRT-532), a channel potentiator (27), reversibly increased CFTRV232D channel activity in perfused inside-out patches. Thus CF caused by defective folding of rare CFTR mutants might be treated with existing CFTR modulators.…”
mentioning
confidence: 99%
“…The P-gp is a heavy glycosylated transmembrane transporter that appears as a double band, a mature fully glycosylated species ($180 kDa) and a core-glycosylated species ($140 kDa). 32,33 We observed not only a direct inhibitory effect on P-gpmediated calcein transport but also a regulatory effect of statins on the protein level of P-gp (Figs. 6 and 7).…”
Section: Cancer Cell Biologymentioning
confidence: 92%
“…It is more likely that altered N-glycans associated with several different proteins affect the drug-resistance mechanisms. P-gp is a heavy N-glycosylated transmembrane transporter that appears as a double band (28,29). Glycosylation of P-gp is important for appropriate protein folding and plasma membrane export.…”
Section: Figmentioning
confidence: 99%